'Mad Men' as a Sonic Symptomatology of Consumer Capitalism. Issue 2 (27th August 2021) - Brooks, Marc
Abstract: One criticism of the television series Mad Men (Matthew Weiner, AMC 2007–15) is that it assumes the form of its subject matter; it offers the same meretricious pleasure as the modern affective advert—atmosphere, emotion, sensuality; getting the joke or reference; solving the puzzle—and nothing of dramatic or critical substance. My main claim here is that three musical moments do initially lead the viewer to believe that the sensuously enjoyable songs—Mozart's 'Voi che sapete', George Jones's 'Cup of Loneliness', and the Beatles' 'Tomorrow Never Knows'—will tie the intricate inter- and intra-textual threads spun in the episode together in the manner of an especially complex affective advert. Through each song, however, the viewer hears how Don's body is distorted, warped, contorted by the consumerist forces that appropriate him, exploit him, and express themselves through him—i.e. it isolates and gathers together a set of symptoms. Rather than offering the momentary, superficial enjoyment of the advert, this sonic symptomatology sends the viewer into interpretative overdrive, seeking both to explain how the ailments arise and to discover therapies that might mitigate them.